Physio-pathological Responses in Japanese Quail Layers to Blood Collection via Cardiac Puncture - Arora , Kashmiri L. (International Journal of Poultry Science, 2011)
The Japanese quail is a very popular animal model for various biomedical disciplines such as growth and development, reproduction, physiology, endocrinology, nutrition, drug testing and toxicology. Hematological and clinical chemistry parameters are important diagnostic tools and experimental studies invariably draw on them for evaluating the outcomes of treatments. For blood collection, a wide variety of sites are utilized for sampling blood from animals including the heart. Cardiac puncture is being practiced in rodents, birds and rabbits particularly when larger quantities are needed for diagnostic and serological work. One should, however, be fully aware of possible complications that may result from this method. On this aspect, information on the post-collection responses are lacking in the Japanese quail. This report highlights some important observations made on the Japanese quail following a one-time collection of blood via cardiac puncture. The results were very considerably variable. Of the nineteen (19) experimental birds used in this project, one (1) bird succumbed to the procedure and died instantaneously and the others (n = 18) experienced some temporary loss in body weight, cessation in egg production and regression of the reproductive organs. The loss in body weight was the maximum by d6 post-collection. At this time (d6), five (5) birds which weighed between 115-118g during the pause and had lost a significant amount of body weight (loss of 12% from the initial weight at day 0) were, after blood collection, euthanized with carbon dioxide and their hearts and reproductive organs were examined and fixed in 10% formalin. Most of the surviving birds (n = 8) regained weight between d3 to d12 post-collection and resumed egg production; however, some birds (n = 2) did not lay eggs even by d12 post collection. Both Hemoglobin (Hb) and Packed Cell Volume (PCV) were significantly elevated during the pause and then returned to their initial values of d0 upon resumption of egg production after the healing process had been compromised. It was implicit that cardiac puncture traumatized the heart and triggered various changes in hormonal and physio-chemical parameters. Post collection pathological alterations included hemopericardium, ventricular hemorrhage and the formation of fibrous tissues in the myocardium and other complications. These points should be kept in mind while planning an experiment or evaluating the outcome of an experiment involving cardiac puncture.